Designing Sustainable Energy for All: Sustainable Product-Service System Design Applied to Distributed Renewable Energy - Vezzoli, Carlo (Green Energy and Technology, 2018)
Design for Sustainability; Product-Service System; Distributed Energy; Renewable Energy; Business Models for DRE Systems